Nostalgic conversations: The co-production of an intervention package for people living with dementia and their spouse. (February 2022) - Dodd, Emily; Ismail, Sanda; Christopher, Gary; Wildschut, Tim; Sedikides, Constantine; Cheston, Richard
Objectives: Nostalgic memories are more social than other forms of autobiographical recall, often refer to atypical events, express more positive affect and reflect life as meaningful. Recalling a nostalgic (compared to ordinary) memory increases self-esteem, self-growth, meaning in life and social connectedness for people living with dementia. We set two objectives: to work with people living with dementia to develop an intervention based on nostalgia, and to assess whether couples could engage in nostalgic conversations. Method: Our research fell into three phases. Initially, we consulted with people living with dementia and with carers to identify the parameters for a nostalgic intervention. From this, we drafted a workbook that contained triggers for nostalgic conversations, which we then took back to the public contributors for refinement. Finally, we trialled the workbook over 5 weeks with six couples, each of which included a person living with dementia. We assessed pre- and post-intervention self-esteem, self-growth, meaning in life and social connectedness for participants with dementia and social connectedness for carers. We then calculated Reliable Change Index scores and established levels of clinically significant change. We also interviewed couples at the end of the intervention to explore its implementation and acceptability. Results: All six couples could identify nostalgic memories, with five couples successfully integrating the nostalgic conversations into their day-to-day lives. A sixth couple found it difficult to engage fully with the intervention, but still considered it useful. All six couples manifested a reliable change in at least one outcome, with one couple showing reliable change across three outcomes. Conclusion: The psychological benefits of nostalgia have been robustly demonstrated in laboratory-based studies. This co-production of an intervention that sets nostalgic recall into the context of a conversation has clinical potential but requires further investigation through a larger study.